Arabic verbs which haven’t subject - al - Salami, Mawtullah bin Awad (Journal of Humanities & Social Sciences, 2019)
According to the well-known grammatical rule (every act must be done by an actor)، there are statements that contradict this rule to say that there are acts that do not have an actor. These opinions were summed up in four sections This research studied by surveying and presenting the opinions of the various grammarians. The study concluded that most of the grammarians agreed that the excess (Kan) and verbs that follow with the excess (ma) have no actors but it said that is not applicable to (Hasha). and in regard to what is stated in the section of verbal assertion، the study concluded that it is due to the image of the act and its purpose.
Keywords: verb; subject; Arabic grammar